Disribution of helminths in quails (coturnix coturnix) and partridges (Alectoris graeca) in the vicinities of Elazi? and Tunceli - Köro?lu, Ergün; Taşan, Erol (Scientific and Technical Research Council of Turkey, 1996)
A total of 100 quails (Coturnix coturnix) from the rural districts of Elazi? and 50 partridges (Alectoris graeca) from Elazi? and Tunceli provinces were obtained in the 1991 and 1992 hunting seasons. All internal organs and body cavities of these birds were examined for helminths species. Except for Corrigia corrigia which was found in pancreas canals of partridges, all the other species were detected in the digestive tracts of these birds. Forty four percent of the quails and sixty six percent of the partridges were found to be infected by various species of helminths. Parasites found in quails and partridges were as fallows : In quails : Choanotaenia infundibulum (39%), Fimbriaria fasciolaris (1%), Lyruterina nigropunctata (4%), Raillietina echinobothrida (1%), R. tetragona (2%), Heterakis gallinarum (1%), Pseudaspidodera pavonis (2%) and Subulura differens (4%). In partridges : Corrigia corrigia (10%), Choanotaenia infundibulum (4%), Raillietina echinobothrida (10%), R. tetragona (6%), Cheiliospirura spinosa (14%), Heterakis dispar (38%), H. gallinarum (12%), Subulura differens (19%), Seurocrynea colini (2%) and S. eurycerca (2%). The presence of L. nigropunctata and P. pavonis in the quails; C. spinosa and S. colini in partridges in Turkey was revealed for the first time in this study.
Elazi? ve Tunceli Yörelerinde Bildircin (Coturnix coturnix) ve Keklik (Alectoris graeca)'lerde Bulunan Helmint Türleri ve Bunlarin Yayilişi
Keywords: Helminth; Partridge; Quail